The Influence of Financial Ratio and Beta on Share Ownership by Foreign Investors in Companies Listed on ISSI : (Indonesia Sharia Stock Index) - Awwal, Muhammad Al Faridho; Lubina, Lia (International Journal of Business, Law, and Education, 2024)
This study aims to analyze the effect of financial ratios (EPS, PER, PBV, ROE, DER and Dividend Yield) and beta on share ownership by foreign investors in companies listed on ISSI (Indonesian Sharia Stock Index). The data used is panel data. The tool used to test the data is using Stata version 14.2. The sample data analyzed were 36 samples. From the analysis it was found that the EPS and DER variables had a significant positive effect on share ownership by foreign investors in companies registered with ISSI. The PER, PBV, ROE, DER, Dividend Yield and beta variables do not have an influence on the company's share ownership by foreign investors in companies registered with ISSI.